THE IMPORTANCE OF LEARNING ENGLISH IN THE MODERN WORLD - Soliyeva Sevinch Jaloliddin qizi,; Xayrilloyeva Aziza Olimjon qizi,; Zaripova Aziza Shaxobiddinovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: In today’s world, with cultural borders becoming increasingly blurred, English has emerged as the dominant global language. Many countries have their own native language, but English serves as a common tongue for international communication. Spoken by major nations such as England, America, and Australia, English has become the primary language taught in international schools and is essential for those aspiring for a brighter future.This article examines the social, educational, economic, and technological importance of learning English in the modern world. It also evaluates the role of English as a global lingua franca and highlights challenges faced by learners and education systems. Recommendations for improving English language teaching methodologies are presented.